2022
DOI: 10.1371/journal.pgph.0000516
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety and stress among high school students: A cross-sectional study in an urban municipality of Kathmandu, Nepal

Abstract: Depression and anxiety are the most widely recognized mental issues affecting youths. It is extremely important to investigate the burden and associated risk factors of these common mental disorders to combat them. Therefore, this study was undertaken with the aim to estimate the prevalence and identify factors associated with depression, anxiety, and stress among high school students in an urban municipality of Kathmandu, Nepal. A cross-sectional study was conducted among 453 students of five randomly selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
4
11
0
Order By: Relevance
“…Moderately severe and severe forms of the disease were found in 15.2% and 9.1% of the respondents respectively. et al, 2021), 47.3% in high school students in Manipur, India (Khongwir et al, 2020), and 56.5% in high school students in Kathmandu, Nepal (Karki et al, 2022). The current finding is also consistent with that of Zhang et al (2020) who in a cross-sectional survey among high school students in Shandong Province, China, reported that 52.4% of them had depression.…”
Section: Prevalence Of Depression Based On Severitysupporting
confidence: 85%
See 1 more Smart Citation
“…Moderately severe and severe forms of the disease were found in 15.2% and 9.1% of the respondents respectively. et al, 2021), 47.3% in high school students in Manipur, India (Khongwir et al, 2020), and 56.5% in high school students in Kathmandu, Nepal (Karki et al, 2022). The current finding is also consistent with that of Zhang et al (2020) who in a cross-sectional survey among high school students in Shandong Province, China, reported that 52.4% of them had depression.…”
Section: Prevalence Of Depression Based On Severitysupporting
confidence: 85%
“…Moreover, the largest proportion of the respondents came from rural communities and the change of environment (from a rural to an urban community) and perhaps the inability to cope with the stresses associated with this transition, especially in the first few weeks, could have also contributed to the current findings. Similar observations were made in a study among high school students in an urban municipality of Kathmandu, Nepal (Karki et al, 2022). It is important, however, to emphasize that these tentative assumption are but not an exhaustive list of the possible causes of the high rate of depression in the current study, given that several other factors play a significant role in the occurrence of depression in adolescence.…”
Section: Prevalence Of Depression Based On Severitysupporting
confidence: 80%
“…A similar study by Karki et al (2022) found to have more than half of the students had depression and anxiety symptoms and nearly one-third of the students had stress symptoms. Prevention and control activities such as schoolbased counseling services focusing to reduce and manage depression, anxiety, and stress faced by the students were recommended.…”
Section: Literature Reviewmentioning
confidence: 71%
“…This study provides evidence that a higher level of academic pressure was positively associated with anxiety symptoms among adolescents, even after adjusting for age, sex, BMI, cortisol, living arrangement, classmate relations, and teacher-classmate relations. Similarly, Zhu et al found a positive correlation between academic pressure and anxiety symptoms among Chinese adolescents [ 16 ], Karki et al reported a significant association between perceived academic pressure and anxiety symptoms among high school students in Nepal [ 42 ], and Trevethan et al observed a longitudinal direct effect of academic pressure on changes in symptoms of generalized anxiety and panic [ 43 ]. According to Lazarus’s cognitive appraisal theory, stress is seen as a relation between individuals and their environment [ 44 ].…”
Section: Discussionmentioning
confidence: 99%